IMT Skills of the pre-service teachers in Cebu City - Helen B. Boholano (International Journal of Evaluation and Research in Education (IJERE), 2018)
Information, media and technology is an essential skill in the 21st century. The development of the country relies on the people. The preservice teachers are task to mold the 21st century learners. The purpose of this study is to investigate and analyze the information, media and technology skills in the 21st century of the preservice teachers in the different Higher Education Institutions (HEIs) in Cebu City. Findings revealed that the preservice teachers possessed very IMT good skills.  There are three themes formulated regarding the effects of new digital technologies in the 21st century instruction. Making taking and learning more convenient with the use of technology, the 21st century role of modern technology in teaching and learning and using technology as tool in research are essential in the 21st century undertakings. Thus, ICTs have been very useful in the teaching-learning process and it has been the modernize way of education which caught the interest of everybody. The effective use of technology enables the preservice teachers to facilitate and adjust their instructional strategies to optimize students’ learning.